Political culture and political consciousness - Natela Basilashvili (Genius Journals, 2021)
Political culture is a very specific type of spiritual culture of society. The political culture includes, expresses the formation of a mechanism for purposeful political activity, the regulation of political relations.
Keywords: Politics; state; power; society